Avoidance of Double Taxation in the Area of Income Tax in Latvia - Lazdiņš, Jānis; Ketners, Kārlis (Journal of the University of Latvia. Law, 2019)
The article is dedicated to the experience of preventing double taxation in the Republic of Latvia, the area of income tax. This topic is made relevant by the tax reform implemented in 2018. Although the payment of income tax has been conceptually changed, the authors propose the thesis regarding a constant approach to prevention of double taxation, based on recommendations by the Organisation for Economic Co-operation and Development (hereinafter – OECD). In the framework of income tax reform, additional requirements have been integrated into regulatory enactments to eliminate the possibility of tax evasion.